Dignostic Utility of HBME1 to Differentiate Between Reactive Mesothelial Cells and Adenocarcinoma Cells in Body Fluids - Gore, Charusheela; Patel, Karan; Bavikar, Rupali R; Koshy, Ashily (Annals of Pathology and Laboratory Medicine, 2018)
Background : Reactive mesothelial cells show overlapping features with malignant cells.To differentiate between the two Immunocytochemistry (ICC) can be used.HBME1 is the antigen present on mesothelial cells.We have tried to evaluate the efficacy of HBME1 to differentiate between reactive mesothelial cells and adenocarcinoma cells. Methods : Total 60 cases with clinical dilemma or suspicious on conventional cytology were selected .Cell block was prepared and staining with monoclonal antibody HBME1 was done.Staining pattern was classified as cytoplasmic ,membranous or combined. Result : Out of 42 ,28 cases showed negative staining ,8 cases showed cytoplasmic positivity and 4 cases showed combined positivity.All the benign cases showed membranous potivity. Conclusion:The staining pattern of HBME1 can be used to differentiate between reactive mesothelial cells and adenocarcinoma cells.